2021
DOI: 10.3390/cancers13133130
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Opportunities to Target DNA Double-Strand Breaks Repair and Replicative Stress Responses to Improve Therapeutic Index of Colorectal Cancer

Abstract: Despite the ample improvements of CRC molecular landscape, the therapeutic options still rely on conventional chemotherapy-based regimens for early disease, and few targeted agents are recommended for clinical use in the metastatic setting. Moreover, the impact of cytotoxic, targeted agents, and immunotherapy combinations in the metastatic scenario is not fully satisfactory, especially the outcomes for patients who develop resistance to these treatments need to be improved. Here, we examine the opportunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 273 publications
(349 reference statements)
0
11
0
Order By: Relevance
“…The collision of unrepaired single-strand lesions with the replication fork along with replication stalling due to replication firing (often oncogene driven) with inadequate nucleotide supply causes RS [ 2 ]. RS is also resolved by HRR and is an important activator of ATR, CHK1 and WEE1 signalling to cell cycle arrest [ 21 ].…”
Section: Double Strand Damagementioning
confidence: 99%
“…The collision of unrepaired single-strand lesions with the replication fork along with replication stalling due to replication firing (often oncogene driven) with inadequate nucleotide supply causes RS [ 2 ]. RS is also resolved by HRR and is an important activator of ATR, CHK1 and WEE1 signalling to cell cycle arrest [ 21 ].…”
Section: Double Strand Damagementioning
confidence: 99%
“…DNA damage repair mechanisms include base excision repair (BER), mismatch repair (MMR), and homologous recombination (HR). These mechanisms identify and correct DNA damage caused by multiple factors such as reactive oxygen species (ROS), radiation, and chemicals ( 31 , 32 ). DNA damage repair, not only removes the damaged cells but also assists in drug resistance ( Figure 2 ) ( 33 , 34 ).…”
Section: Tcm Reverses the Chemoresistance Of Crc And Inhibits Tumor G...mentioning
confidence: 99%
“…Second, PARP inhibitors inhibit the repair of NHEJ, leading to cell apoptosis or necrosis after DNA damage occurs (Gupta et al, 2018). Third, some new studies have shown that PARP inhibitors reduce the repair efficiency of MMEJ, an auxiliary DNA repair mechanism (Tomasini et al, 2021). This speeds up the process of apoptosis, or death, in cancer cells that do not initiate the required DNA repair.…”
Section: Dna-damaging Agents In Gastric Cancermentioning
confidence: 99%